An Overview of Learning Motivation Among Students Working as Tin Miners - Sigra Tan Magita; Satiningsih (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
The phenomenon of tin mining among students on Bangka Island is prevalent. The abundance of tin resources and the ease of access to mining activities have led to the widespread involvement of students in mining operations. The practice of tin mining among students raises concerns that it may diminish their motivation to learn, thereby threatening their future prospects. This study aims to explore the learning motivation of students who work as tin miners. A qualitative case study approach was employed to investigate this issue. Data were collected through in-depth interviews with three high school students actively engaged in tin mining. Thematic analysis was conducted on the interview data, and source triangulation was used to ensure the validity of the findings. The study revealed that the students involved in tin mining exhibited low learning motivation due to the limited time and energy available to them as a result of their working conditions.